The regime of 'post-truth': COVID-19 and the politics of knowledge. Issue 1 (2nd January 2023) - Kwok, Henry; Singh, Parlo; Heimans, Stephen
ABSTRACT: The emergence of 'post-truth' is often associated with the rise of conspiracy theories and the lack of trust in scientific knowledge. This article attempts to theorise the complex division of labour in this regime of 'post-truth', with reference to the COVID-19 pandemic/infodemic. First, we argue that the 'post-truth' condition mirrors what Foucault called the 'will to truth', and that this challenges the procedures and systems by which truth and knowledge are ordered. Second, through Basil Bernstein's extension of Foucault's work, we argue that the era of post-truth has two features regarding the condition of knowledge: (1) that conflicts in the field of knowledge recontextualisation, that is, the pedagogisation of knowledge, are becoming more intense and visible, and (2) that greater exposure to high-stakes, uncertain scientific knowledge, which grows at exponential rate, increases social anxieties and leads to biopoliticisation of neoliberal responsibilisation.